The Contribution to Understanding the Study of Psycholinguistics in Facilitating Balaghah Learning - Sokip, Sokip; Nurcholis, Ahmad; Kojin, Kojin; Faizin, Muhammad Zaenal; Hanifa, Abu (Universitas Islam Negeri Raden Intan Lampung, 2023)
The difficulty of the dauq al-lughat approach to be applied in balaghah learning for non-Arabic speakers like Indonesia raised alternative psycholinguistic approaches as a follow-up in maximizing language acquisition and language production. This article intended to conduct in-depth research on the urgency of psycholinguistics, especially in Balaghah learning. Library research was the research method of this article. Primary data sources were the book entitled ”An Introduction to Psycholinguistics” by Steinberg and Natalia and ”Jawahirul Balaghah” by Sayyid Ahmad Al-Hasyimy. The source of secondary data were obtained from other books and journals related to psycholinguistics and balaghah learning. Data collection techniques were carried out through two ways of reading data, namely symbolic level and semantic level. Data analysis techniques included data reduction, data display and conclusion drawing/verification. This article showed that the important role of psycholinguistics in balaghah learning was to examine the background of the problem from errors in understanding the meaning of language and the steps for handling it (problem solving). Psycholinguistic implications in learning Balaghah was to provide a more effective learning atmosphere in strengthening students’ competence and to encourage students’ achievement.